2020
DOI: 10.1002/acm2.12844
|View full text |Cite
|
Sign up to set email alerts
|

Difference in LET‐based biological doses between IMPT optimization techniques: Robust and PTV‐based optimizations

Abstract: Purpose: While a large amount of experimental data suggest that the proton relative biological effectiveness (RBE) varies with both physical and biological parameters, current commercial treatment planning systems (TPS) use the constant RBE instead of variable RBE models, neglecting the dependence of RBE on the linear energy transfer (LET). To conduct as accurate a clinical evaluation as possible in this circumstance, it is desirable that the dosimetric parameters derived by TPS (D RBE¼1:1 ) are close to the "… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…One limitation of the present study is that robust optimization was not incorporated in the tested planning approaches. It has been suggested that robust optimization (against physical uncertainties) might reduce the impact of variable RBE 50,51 . Variable RBE optimization is particularly suitable for existing robust optimization methods developed for IMPT planning.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One limitation of the present study is that robust optimization was not incorporated in the tested planning approaches. It has been suggested that robust optimization (against physical uncertainties) might reduce the impact of variable RBE 50,51 . Variable RBE optimization is particularly suitable for existing robust optimization methods developed for IMPT planning.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that robust optimization (against physical uncertainties) might reduce the impact of variable RBE. 50 , 51 Variable RBE optimization is particularly suitable for existing robust optimization methods developed for IMPT planning. One only needs to replace constant RBE with variable RBE in the optimization criteria.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies have been carried out to evaluate the dosimetric effects of different RBE models in passive scattering proton therapy [ 80 ], and IMPT plans for numerous tumor sites including H&N [ 81 85 ], thorax [ 84 , 86 ], liver [ 81 ], prostate [ 84 , 87 , 88 ], and craniospinal irradiations [ 89 ]. Tilly et al [ 68 ] first reported the influence on the dose volume histograms after RBE correction for a patient with hypopharynx cancer.…”
Section: Use Of Let In Handn Plan Evaluation and Patient Outcome Studymentioning
confidence: 99%
“…Both studies indicated increased RBE doses at nearby OARs, compared to that using fixed RBE of 1.1. In addition, compared to planning target volume (PTV)–based optimization, robust optimization plans showed that dose distributions calculated with fixed-RBE of 1.1 were closer to the biological doses calculated with variant RBE models [ 85 ]. All these studies revealed dosimetric uncertainties of using different RBE models, as well as possible interpatient variations when applying RBE models.…”
Section: Use Of Let In Handn Plan Evaluation and Patient Outcome Studymentioning
confidence: 99%